2016
DOI: 10.1093/humrep/dew325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment with oral contraceptives and progestins on IVF outcomes in women with polycystic ovary syndrome

Abstract: STUDY QUESTION: Do oral contraceptives (OCs) and progestins impact live birth rate of IVF when used for cycle scheduling in women with polycystic ovary syndrome (PCOS)?SUMMARY ANSWER: OCs used for scheduling IVF cycle were associated with lowered rates of pregnancy and live birth after fresh embryo transfer, whereas progestins used for this purpose yield higher rates of pregnancy and live birth than OCs.WHAT IS KNOWN ALREADY: Due to oligo-menorrhea in PCOS, OCs and progestin are extensively used to schedule th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
(32 reference statements)
3
31
1
Order By: Relevance
“…Recently, a prospective study by Wei et al reported that menses induction by COC before IVF was associated with higher pregnancy loss rate and lower live-birth rate (36). This study cannot be compared with our study: First, their study endpoints were pregnancy loss rate and live-birth rate, which were not discussed in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Recently, a prospective study by Wei et al reported that menses induction by COC before IVF was associated with higher pregnancy loss rate and lower live-birth rate (36). This study cannot be compared with our study: First, their study endpoints were pregnancy loss rate and live-birth rate, which were not discussed in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…However, a secondary analysis of our data collected in the randomized trial revealed that oral contraceptives for such purpose had an adverse effect on outcome of fresh embryo transfer in terms of the rates of pregnancy and live birth. 6 In contrast, such effect of oral contraceptives was greatly diminished by performing freeze-all and frozen embryo transfer. 6 Thus, in those cycles with oral contraceptive scheduling, frozen embryo transfer may be a better choice than immediate fresh embryo transfer to achieve live birth, though further studies are needed to obtain a confirmed conclusion.…”
Section: Pregnancy Pregnancy Loss and Live Birthmentioning
confidence: 99%
“…6 In contrast, such effect of oral contraceptives was greatly diminished by performing freeze-all and frozen embryo transfer. 6 Thus, in those cycles with oral contraceptive scheduling, frozen embryo transfer may be a better choice than immediate fresh embryo transfer to achieve live birth, though further studies are needed to obtain a confirmed conclusion.…”
Section: Pregnancy Pregnancy Loss and Live Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated the effects of oral contraceptive pretreatment prior to different ovarian stimulation protocols on cycle outcomes, and it has been reported that oral contraceptives used for menses induction prior to the GnRH antagonist protocol are associated with poor outcomes after fresh embryo transfer, including a lower live birth rate, a lower pregnancy rate and a higher pregnancy loss rate (Farquhar et al, 2017;Griesinger et al, 2008;Wei et al, 2017). However, there is still insufficient evidence for the effect of oral contraceptive pretreatment on cycle outcomes in women undergoing the GnRHa long protocol or the GnRHa short protocol.…”
mentioning
confidence: 99%